2020
DOI: 10.3390/ijerph17155534
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Health-Related Behaviors of Adult Korean Women at Normal BMI with Different Body Image Perceptions: Results from the 2013–2017 Korea National Health and Nutrition Examination Survey (KNHNES)

Abstract: The tendency of misperceiving one’s body image was found to be higher among those at normal body mass index (BMI). Thus, the present study aims to provide basic data to seek solutions for ideal physical activities and right body image perception by comparing health-related behaviors of women at normal BMI. Among the 39,225 respondents from the Korea National Health and Nutrition Examination Survey (KNHNES) conducted from 2013 to 2017, 10,798 adult women with World Health Organization (WHO) BMI Classifications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
4
0
3
Order By: Relevance
“…Our results contrast with findings on populations of no industrialized countries and at low socioeconomic levels [ 37 , 39 , 63 ], whereas they are consistent with those observed on populations of industrialized countries or at high socio-economic levels [ 25 , 31 , 37 ]. The ideal of thinness, launched by the fashion industry since the 1960s, has become and still remains the idealized standard of beauty typical of Western cultural values [ 64 ], exerting its influence especially on the female sex.…”
Section: Discussionmentioning
confidence: 99%
“…Our results contrast with findings on populations of no industrialized countries and at low socioeconomic levels [ 37 , 39 , 63 ], whereas they are consistent with those observed on populations of industrialized countries or at high socio-economic levels [ 25 , 31 , 37 ]. The ideal of thinness, launched by the fashion industry since the 1960s, has become and still remains the idealized standard of beauty typical of Western cultural values [ 64 ], exerting its influence especially on the female sex.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, men emerged as a more significant predictor of obesity than women in the Korean adult population aged 19 and over during the COVID-19 pandemic. This can be attributed to the Korean cultural practices in which women overestimate their body image and excessively practice weight management more than men [32]. Accordingly, it is suggested that a multinational joint study should be conducted in order to address the issue of whether gender is a predisposing factor for obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The KNHANES 2013-2017 revealed that 87.6% of Korean female adults misperceived their body image despite having a normal BMI between 18.5-25.0. This was related to unhealthy behaviors, such as smoking, insufficient sleep, and excessive body weight management [34]. Based on the data of patients with prediabetes and DM collected from the Korean Center for Disease Control and Prevention, the better the subjective health status, the higher the ratio of normal weight, proper sleep time, exercise, and eating out among health-related behaviors [35].…”
Section: Discussionmentioning
confidence: 99%